Straw / hydrated magnesium silicate composite material, preparation method and application

By combining straw with hydrated magnesium silicate gel material, the problem of poor compatibility between straw and cement composite materials is solved, and the effective utilization of straw and the performance improvement of composite materials is achieved, including the improvement of flexural strength, water resistance and green and low-carbon properties.

CN119683964APending Publication Date: 2025-03-25SOUTHWEAT UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411907708.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

In the prior art, straw and cement composite materials have poor compatibility problems, resulting in the inability to effectively utilize straw resources and environmental pollution problems such as incineration.

Method used

The straw/hydrated magnesium silicate composite is used to improve the compatibility and performance of the material by combining the straw with the hydrated magnesium silicate gel material, activated magnesium oxide, fume and fly ash as the gelling material components, and polycarboxylic acid water reducer as the water reducer.

Benefits of technology

The effective utilization of straw is achieved, the flexural strength and volume stability of the composite material are improved, the material density is reduced, and the water resistance and green and low-carbon properties of the material are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119683964A_ABST
    Figure CN119683964A_ABST
Patent Text Reader

Abstract

The invention discloses a straw / hydrated magnesium silicate composite material as well as a preparation method and application thereof. The straw / hydrated magnesium silicate composite material comprises the following components in parts by weight: 2-20 parts of straw, 80-98 parts of a cementing material, water and a water reducing agent, the gel material comprises the following components in parts by weight: 40 parts of active magnesium oxide, 12-54 parts of silica fume and 6-48 parts of fly ash; the water reducing agent is a polycarboxylic acid water reducing agent; according to the invention, straw is used as a reinforcing material of a hydrated magnesium silicate gel material, and a low-carbon gel material hydrated magnesium silicate is used as a matrix material, so that good stability of straw fibers in a matrix can be ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of inorganic non-metallic composite materials, and in particular to a straw / hydrated magnesium silicate composite material, a preparation method and application thereof. Background Art

[0002] As global temperatures continue to rise, reducing carbon emissions has become a global consensus. The "dual carbon" goal has become a core issue in my country's new development stage, and it brings certain risks and challenges to high-carbon industries. Portland cement is one of the most important building materials, widely used in industrial and civil buildings, roads, water conservancy and national defense projects. However, according to statistics, about 8% of the world's annual anthropogenic CO2 emissions come from the production of Portland cement. The growing global demand for Portland cement, coupled with the high energy consumption of Portland cement production and its share in global greenhouse gas emissions, have led to the need for new low-carbon cementitious materials in the building materials industry.

[0003] In recent years, magnesium silicate cement, which has excellent mechanical properties, has become a potential, sustainable and technologically advanced alternative to silicate cement due to its low production temperature and significant carbon fixation capacity. Magnesium silicate cement is known as environmentally friendly cement and is believed to help alleviate global warming caused by different industrial activities. The commonly used raw materials of magnesium silicate cement are soluble SiO2 and MgO, and its main hydration products are magnesium hydroxide and hydrated magnesium silicate gel. The crystallinity of hydrated magnesium silicate gel is poor, and the silicon-oxygen tetrahedron is layered, which plays a major role in the compressive strength of the system. A large number of studies have shown that hydrated magnesium silicate cementitious materials have good compressive strength and low pH value (compared with traditional silicate cement), good water resistance (compared with traditional magnesium oxychloride cement), and its hydration products can form enstatite and olivine when calcined. In addition, unlike the system in which magnesium oxide carbide relies on carbonization to increase strength, hydrated magnesium silicate cement can obtain strength through hydration, does not require any special treatment and high carbon dioxide curing environment, and is therefore considered to have potential application prospects in the field of building materials.

[0004] As the most abundant natural polymer material in nature, straw is an easily accessible and economical green renewable resource. According to incomplete statistics, about 800 million tons of crop straw are produced in my country every year, but only about 5% is effectively utilized, and the vast majority is burned on the spot. The repeated illegal burning not only wastes resources, but also buries fire hazards, causes environmental pollution and threatens transportation safety. Although local governments have implemented policies such as increasing subsidies for returning straw to the fields, they have not fundamentally solved the problem of "straw burning".

[0005] There are also studies on compounding straw with cement, but there is generally a problem of poor compatibility between the two. Summary of the invention

[0006] Aiming at the problems existing in the prior art, the present invention provides a straw / hydrated magnesium silicate composite material, a preparation method and application thereof.

[0007] The technical solution adopted by the present invention is:

[0008] A straw / hydrated magnesium silicate composite material, comprising, by weight:

[0009] 2-20 parts of straw, 80-98 parts of cementitious materials, water and water reducing agent;

[0010] The gel material comprises, by weight: 40 parts of active magnesium oxide, 12 to 54 parts of silica fume, and 6 to 48 parts of fly ash;

[0011] The water reducing agent is a polycarboxylic acid water reducing agent.

[0012] Furthermore, in step 1, the mass of water is 40% to 70% of the sum of the mass of the cementitious material and the mass of the straw; and the mass of the water reducing agent is 0.8% to 1.5% of the mass of the cementitious material.

[0013] Furthermore, in step 1, the active magnesium oxide comprises 16 to 36 parts by weight of the first active magnesium oxide and 4 to 24 parts by weight of the second active magnesium oxide;

[0014] The first active magnesium oxide has a MgO content greater than 80 wt.%, and an activity of 65-75%;

[0015] The MgO content in the second active magnesium oxide is greater than 90 wt.%, and its activity is 75-85%.

[0016] Furthermore, the straw is one of rice straw, wheat straw, and corn straw, or a mixture of two or more of them in any proportion.

[0017] Furthermore, the length of the straw is 0.1 to 3 cm.

[0018] Furthermore, the content of amorphous SiO2 in the silica ash is greater than 95wt.%.

[0019] Furthermore, the content of SiO2 in the fly ash is 50-60wt.%, the content of Al2O3 is 20-30wt.%, and the content of CaO is 5-8wt.%.

[0020] A method for preparing a straw / hydrated magnesium silicate composite material comprises the following steps:

[0021] Step 1: Mix the water reducing agent and water to obtain a liquid material;

[0022] Step 2: Stir the gelling material thoroughly; add the liquid material in step 1 to the stirred gelling material, and stir thoroughly to obtain a hydrated magnesium silicate slurry;

[0023] Step 3: adding the straw to the magnesium silicate hydrate slurry in step 2, and stirring thoroughly to obtain a straw / magnesium silicate hydrate slurry;

[0024] Step 4: Pour the straw / hydrated magnesium silicate slurry obtained in step 3 into a mold, vibrate and then cure to obtain the desired straw / hydrated magnesium silicate composite material.

[0025] Furthermore, in step 3, the mixture is first stirred for 30 seconds and then rapidly stirred for 6 minutes.

[0026] An application of a straw / hydrated magnesium silicate composite material, wherein the straw / hydrated magnesium silicate composite material is used as a building material.

[0027] The beneficial effects of the present invention are:

[0028] (1) The present invention uses straw as a reinforcing material for the hydrated magnesium silicate gel material. The addition of straw can improve the flexural strength of the composite material, reduce the density of the product, and improve the volume stability of the product;

[0029] (2) The present invention uses low-carbon gel material hydrated magnesium silicate as the base material, without Ca 2+ The hydration products of ionic and low-alkalinity hydrated magnesium silicate cement, hydrated magnesium silicate gel and Mg(OH)2, have good compatibility with straw, and low-alkalinity hydrated magnesium silicate cement can ensure that the straw fiber has good stability in the matrix;

[0030] (3) The present invention uses polycarboxylic acid water reducer as the water reducer of the composite material, and a large amount of fly ash is added instead of silica fume to improve the fluidity of the composite material slurry and save costs, while further improving and improving the greenness and low carbonization of the material;

[0031] (4) The composite material prepared by the present invention can be cured in water, which is different from the traditional magnesium oxychloride cement. The composite material prepared by the present invention uses hydrated magnesium silicate cementitious material as the matrix material, so that the product has good water resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 It is a schematic cross-sectional view of the composite material samples obtained in Comparative Example 1, Example 7, and Examples 10 to 12 of the present invention.

[0033] Figure 2 The cross-sectional macroscopic morphology of the composite materials obtained in Comparative Example 1 and Example 7 of the present invention at different curing ages are shown.

[0034] Figure 3The XRD diagram of the composite material obtained in Example 7 of the present invention at different curing ages.

[0035] Figure 4 This is the XRD diagram of the composite material of rice straw at different curing ages in the composite material obtained in Example 7 of the present invention. DETAILED DESCRIPTION

[0036] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments.

[0037] A straw / hydrated magnesium silicate composite material, comprising, by weight:

[0038] 2 to 20 parts of straw, 80 to 98 parts of cementitious material, water and water reducing agent; the mass of water is 40% to 70% of the sum of the mass of cementitious material and straw; the mass of water reducing agent is 0.8% to 1.5% of the mass of cementitious material. The straw is one or two or more of rice straw, wheat straw and corn straw mixed in any proportion. The length of the straw is 0.1 to 3 cm.

[0039] The gel material comprises, by weight: 40 parts of active magnesium oxide, 12 to 54 parts of silica fume, and 6 to 48 parts of fly ash; the active magnesium oxide comprises, by weight: 16 to 36 parts of a first active magnesium oxide and 4 to 24 parts of a second active magnesium oxide;

[0040] The first active magnesium oxide has a MgO content greater than 80 wt.%, and an activity of 65-75%;

[0041] The MgO content in the second active magnesium oxide is greater than 90 wt.%, and its activity is 75-85%.

[0042] The content of amorphous SiO2 in silica ash is greater than 95wt%. The content of SiO2 in fly ash is 50-60wt%. The content of Al2O3 is 20-30wt%. The content of CaO is 5-8wt%. The selection of fly ash and silica ash only needs to meet the above requirements.

[0043] The water reducing agent is a polycarboxylic acid water reducing agent.

[0044] A method for preparing a straw / hydrated magnesium silicate composite material comprises the following steps:

[0045] Step 1: Mix the water reducing agent and water to obtain a liquid material;

[0046] Step 2: Stir the gelling material thoroughly (stir at a low speed for 1 minute); add the liquid material in step 1 to the stirred gelling material (add within 30 seconds), and stir thoroughly (stir at a low speed for 3 minutes) to obtain a hydrated magnesium silicate slurry;

[0047] Step 3: adding the straw to the hydrated magnesium silicate slurry in step 2, and stirring thoroughly (first stirring for 30 seconds, then rapidly stirring for 6 minutes) to obtain a straw / hydrated magnesium silicate slurry;

[0048] Step 4: Pour the straw / hydrated magnesium silicate slurry obtained in step 3 into a mold, vibrate (vibrate for 30 seconds), and cure for 24 hours. After demoulding, cure under curing conditions to a specified age to obtain the desired straw / hydrated magnesium silicate composite material. The curing can be standard curing, steam curing, carbon curing, or water curing, any one of which can be selected.

[0049] Example 1

[0050] A straw / hydrated magnesium silicate composite material, comprising, by weight:

[0051] 6 parts of rice straw with a length of 0.4 to 0.6 cm, 94 parts of cementitious materials, water and polycarboxylic acid water reducer; the mass of water is 50% of the sum of the mass of cementitious materials and rice straw; the mass of polycarboxylic acid water reducer is 1% of the mass of cementitious materials.

[0052] The cementitious materials include 40 parts of active magnesium oxide, 54 parts of silica fume and 6 parts of fly ash;

[0053] 32 parts of the first active magnesium oxide and 8 parts of the second active magnesium oxide;

[0054] The first active magnesium oxide has a MgO content greater than 80 wt.%, and an activity of 65-75%;

[0055] The MgO content in the second active magnesium oxide is greater than 90 wt.%, and its activity is 75-85%.

[0056] A method for preparing a straw / hydrated magnesium silicate composite material comprises the following steps:

[0057] Step 1: Mix the water reducing agent and water to obtain a liquid material;

[0058] Step 2: Stir the gelling material thoroughly (stir at a low speed for 1 minute); add the liquid material in step 1 to the stirred gelling material (add within 30 seconds), and stir thoroughly (stir at a low speed for 3 minutes) to obtain a hydrated magnesium silicate slurry;

[0059] Step 3: adding the straw to the hydrated magnesium silicate slurry in step 2, and stirring thoroughly (first stirring for 30 seconds, then rapidly stirring for 6 minutes) to obtain a straw / hydrated magnesium silicate slurry;

[0060] Step 4: Pour the straw / hydrated magnesium silicate slurry obtained in step 3 into a mold, vibrate (vibrate for 30 seconds), and cure for 24 hours. After demoulding, cure under curing conditions to a specified age to obtain the desired straw / hydrated magnesium silicate composite material. The curing can be standard curing, steam curing, carbon curing, or water curing, any one of which can be selected.

[0061] After testing, the fluidity of this embodiment is 285mm, the initial setting time is 50min, the final setting time is 100min, the compressive strength after standard curing for 7 days is 19.4MPa, and the compressive strength after standard curing for 28 days is 33.0MPa.

[0062] Example 2

[0063] The other steps of this embodiment are the same as those of embodiment 1, except that the cementitious material includes 40 parts of active magnesium oxide, 54 parts of silica fume, and 6 parts of fly ash;

[0064] 24 parts of the first active magnesium oxide and 16 parts of the second active magnesium oxide;

[0065] After testing, the fluidity of this embodiment is 200 mm, the initial setting time is 10 min, the final setting time is 15 min, the compressive strength after standard curing for 7 days is 13.2 MPa, and the compressive strength after standard curing for 28 days is 14.8 MPa.

[0066] Example 3

[0067] The other steps of this embodiment are the same as those of embodiment 1, except that the cementitious material includes 40 parts of active magnesium oxide, 54 parts of silica fume, and 6 parts of fly ash;

[0068] 16 parts of the first active magnesium oxide and 24 parts of the second active magnesium oxide;

[0069] After testing, the fluidity of this embodiment is 70 mm, the initial setting time is 5 min, the final setting time is 10 min, the compressive strength after standard curing for 7 days is 9.1 MPa, and the compressive strength after standard curing for 28 days is 19.8 MPa.

[0070] Example 4

[0071] The other steps of this embodiment are the same as those of embodiment 1, except that the cementitious material includes 40 parts of active magnesium oxide, 5 parts of silica fume, and 6 parts of fly ash;

[0072] 8 parts of the first active magnesium oxide and 32 parts of the second active magnesium oxide;

[0073] After testing, the fluidity of this embodiment is 0 mm, the initial setting time is 1 min, the final setting time is 4 min, the compressive strength after standard curing for 7 days is 6.5 MPa, and the compressive strength after standard curing for 28 days is 18.6 MPa.

[0074] Example 5

[0075] The other steps of this embodiment are the same as those of embodiment 1, except that the cementitious material includes 40 parts of active magnesium oxide, 48 parts of silica fume, and 12 parts of fly ash;

[0076] 24 parts of the first active magnesium oxide and 16 parts of the second active magnesium oxide;

[0077] After testing, the fluidity of this embodiment is 230 mm, the initial setting time is 15 min, the final setting time is 30 min, the compressive strength after standard curing for 7 days is 16.3 MPa, and the compressive strength after standard curing for 28 days is 26.4 MPa.

[0078] Example 6

[0079] The other steps of this embodiment are the same as those of embodiment 5, except that the cementitious material includes 40 parts of active magnesium oxide, 36 parts of silica fume, and 24 parts of fly ash;

[0080] After testing, the fluidity of this embodiment is 270 mm, the initial setting time is 30 min, the final setting time is 90 min, the compressive strength after standard curing for 7 days is 18.9 MPa, and the compressive strength after standard curing for 28 days is 33.0 MPa.

[0081] Example 7

[0082] The other steps of this embodiment are the same as those of embodiment 5 except that the cementitious material includes 40 parts of active magnesium oxide, 30 parts of silica fume, and 30 parts of fly ash;

[0083] After testing, the fluidity of this embodiment is 320 mm, the initial setting time is 50 min, the final setting time is 115 min, the compressive strength after standard curing for 7 days is 13.5 MPa, and the compressive strength after standard curing for 28 days is 32.4 MPa.

[0084] Example 8

[0085] The other steps of this embodiment are the same as those of embodiment 5, except that the cementitious material includes 40 parts of active magnesium oxide, 24 parts of silica fume, and 36 parts of fly ash;

[0086] After testing, the fluidity of this embodiment is 380 mm, the initial setting time is 125 min, the final setting time is 170 min, the compressive strength after standard curing for 7 days is 10.3 MPa, and the compressive strength after standard curing for 28 days is 25.2 MPa.

[0087] Example 9

[0088] The other steps of this embodiment are the same as those of embodiment 5, except that the cementitious material includes 40 parts of active magnesium oxide, 12 parts of silica fume, and 48 parts of fly ash;

[0089] After testing, the fluidity of this embodiment is 490 mm, the initial setting time is 195 min, the final setting time is 240 min, the compressive strength after standard curing for 7 days is 4.0 MPa, and the compressive strength after standard curing for 28 days is 11.6 MPa.

[0090] Example 10

[0091] The other steps of this embodiment are the same as those of embodiment 7, except that 2 portions of rice straw with a diameter of 0.4 to 0.6 cm are used.

[0092] Embodiment 11

[0093] The other steps of this embodiment are the same as those of embodiment 7, except that 4 portions of rice straw with a diameter of 0.4 to 0.6 cm are used.

[0094] Example 12

[0095] The other steps of this embodiment are the same as those of embodiment 7, except that 8 portions of rice straw with a diameter of 0.4 to 0.6 cm are used.

[0096] Example 13

[0097] The other steps of this embodiment are the same as those of embodiment 7, except that 1-2 cm wheat straw is used, the mass of water is 70% of the mass of the cementitious material, and the mass of the polycarboxylate water reducer is 1.5% of the mass of the cementitious material.

[0098] Embodiment 14

[0099] The other steps of this embodiment are the same as those of embodiment 7, except that 2-3 cm corn stalks are used, the mass of water is 40% of the mass of the cementitious material, and the mass of the polycarboxylate water reducer is 0.8% of the mass of the cementitious material.

[0100] Comparative Example 1

[0101] The other steps of this comparative example are the same as those of Example 7, except that rice straw is not included.

[0102] Comparative Example 2

[0103] The other steps of this comparative example are the same as those of Example 1, except that 40 parts of the first active magnesium oxide are used, and the second active magnesium oxide is not included.

[0104] After testing, the fluidity of this embodiment is 400 mm, the initial setting time is 2040 min, the final setting time is 2365 min, the compressive strength after standard curing for 7 days is 11.7 MPa, and the compressive strength after standard curing for 28 days is 30.3 MPa.

[0105] Comparative Example 3

[0106] The other steps of this comparative example are the same as those of Example 1, except that 40 parts of the second active magnesium oxide are used, and the first active magnesium oxide is not included.

[0107] After testing, the fluidity of this embodiment is 0 mm, the initial setting time is 0 min, the final setting time is 0 min, the compressive strength after standard curing for 7 days is 3.2 MPa, and the compressive strength after standard curing for 28 days is 13.0 MPa.

[0108] Comparative Example 4

[0109] The other steps of this comparative example are the same as those of Example 5, except that 60 parts of silica fume are used and fly ash is not included.

[0110] After testing, the fluidity of this embodiment is 200 mm, the initial setting time is 10 min, the final setting time is 15 min, the compressive strength after standard curing for 7 days is 13.2 MPa, and the compressive strength after standard curing for 28 days is 14.8 MPa.

[0111] Comparative Example 5

[0112] The other steps of this comparative example are the same as those of Example 5, except that 60 parts of fly ash are used and silica fume is not included.

[0113] After testing, the fluidity of this embodiment is 640mm, the initial setting time is 1600min, the final setting time is 2060min, the compressive strength after standard curing for 7 days is 0.3MPa, and the compressive strength after standard curing for 28 days is 3.0MPa.

[0114] Figure 1 The cross-sectional macroscopic morphology and microscope magnified images of the composite materials obtained in Comparative Example 1 and Example 7 and Examples 10 to 12 of the present invention after the flexural strength test. In the figure, a is the result of Comparative Example 1, b is the result of Example 10, c is the result of Example 11, d is the result of Example 7, and e is the result of Example 12.

[0115] It can be seen from the figure that rice straw is evenly dispersed in the hydrated magnesium silicate matrix and has good bonding strength.

[0116] Figure 2 The composite materials obtained in Comparative Example 1 and Example 7 of the present invention are cross-sectional macroscopic morphology diagrams of the composite materials at different curing ages. In the figure, A is the result of Comparative Example 1, and B is the result of Example 7.

[0117] Among them, a~e are the results of the comparative example at the curing ages of 7d, 28d, 56d, 90d and 270d respectively.

[0118] It can be seen from the figure that with the increase of curing age, until the age of 270 days, the straw still maintains a relatively complete form in the magnesium silicate hydrate matrix, which fully demonstrates that the straw has good stability in the magnesium silicate hydrate system.

[0119] Figure 3 This is the XRD diagram of Example 7 of the present invention at different curing ages. It can be seen from the figure that obvious amorphous MSH gel peaks appear at 2θ of 18-28°, 34-38° and 58-62°. As the curing age increases, the diffraction peaks of the MSH gel become more and more obvious, which indicates that as the curing age increases, more and more MSH gel is generated.

[0120] As the curing age gradually increases, the Mg(OH)2 diffraction peak gradually weakens, indicating that Mg(OH)2 has been hydrating with the active SiO2 in the siliceous raw material, resulting in the consumption of Mg(OH)2. In addition, the diffraction peak of MgO almost disappears at the age of 28 days, indicating that the active MgO in the composite material is basically completely involved in the hydration reaction after the curing age exceeds 28 days, generating Mg(OH)2 and amorphous MSH gel. After the age exceeds 28 days, Mg(OH)2 is mainly consumed and cannot be replenished, resulting in the gradual decrease in the intensity of the Mg(OH)2 diffraction peak. Mullite and quartz in the composite material are stable substances that are difficult to react at room temperature and pressure. Therefore, at the age of 270 days, there are still obvious quartz and mullite diffraction peak intensities.

[0121] Figure 4 The XRD diagram of the rice straw in the composite material obtained in Example 7 of the present invention at different curing ages shows that relatively obvious Mg(OH)2 diffraction peaks appear near 2θ of 18° and 38°; obvious diffraction peaks appear near 2θ of 16° and 22°, which are diffraction peaks caused by amorphous cellulose, hemicellulose and lignin in the rice straw. From the diffraction peak of Mg(OH)2, it can be seen that as the curing age is from 7d to 28d, the Mg(OH)2 diffraction peak appears to be enhanced, indicating that new Mg(OH)2 is generated; and when the curing age is from 28d to 270d, the Mg(OH)2 diffraction peak appears to be weakened, indicating that Mg(OH)2 is consumed. In addition, the cleanliness percentage and cleanliness index of the rice straw in the composite material have not changed much, indicating that the rice straw fiber has good stability in the hydrated magnesium silicate matrix.

[0122] The present invention uses straw as a reinforcing material for hydrated magnesium silicate gelling material. The addition of straw can improve the flexural strength of the composite material, reduce the density of the product, and improve the volume stability of the product. The volume density of the finished product obtained by the present invention is 0.85-1.26 g / cm3 Compared with the pure hydrated magnesium silicate paste, the flexural strength of the composite material can be increased by 64.9% at most. Therefore, the present invention is an effective way to realize the utilization of straw. The present invention uses the new low-carbon cementitious material hydrated magnesium silicate as the matrix material, without Ca 2+ The hydration products of ionic and low-alkalinity magnesium silicate cement, hydrated magnesium silicate gel and Mg(OH)2, have good compatibility with straw, and low-alkalinity magnesium silicate cement can ensure that the straw fiber has good stability in the matrix. In addition, the preparation of magnesium silicate hydrate cementitious material by mixing two magnesium oxides with different activities can not only ensure the working performance (fluidity, setting time, etc.) of the prepared magnesium silicate hydrate cementitious material slurry, but also ensure the mechanical properties of the magnesium silicate hydrate cementitious material. The large amount of fly ash instead of silica fume can further improve and improve the greenness and low carbonization of the material while improving the fluidity of the composite material slurry and saving costs.

Claims

1. A straw / hydrated magnesium silicate composite material, characterized in that: The parts by weight include: 2-20 parts of straw, 80-98 parts of cementitious materials, water and water reducing agent; The gel material comprises, by weight: 40 parts of active magnesium oxide, 12 to 54 parts of silica fume, and 6 to 48 parts of fly ash; The water reducing agent is a polycarboxylic acid water reducing agent.

2. A straw / hydrated magnesium silicate composite material according to claim 1, characterized in that: In step 1, the mass of water is 40% to 70% of the sum of the mass of the cementitious material and the mass of the straw; the mass of the water reducing agent is 0.8% to 1.5% of the mass of the cementitious material.

3. The straw / hydrated magnesium silicate composite material according to claim 1, characterized in that: In step 1, the active magnesium oxide includes 16 to 36 parts by weight of the first active magnesium oxide and 4 to 24 parts by weight of the second active magnesium oxide; The first active magnesium oxide has a MgO content greater than 80 wt.%, and an activity of 65-75%; The MgO content in the second active magnesium oxide is greater than 90 wt.%, and its activity is 75-85%.

4. The straw / hydrated magnesium silicate composite material according to claim 1, characterized in that: The straw is one of rice straw, wheat straw and corn straw, or a mixture of two or more of them in any proportion.

5. The straw / hydrated magnesium silicate composite material according to claim 1, characterized in that: The length of the straw is 0.1 to 3 cm.

6. The straw / hydrated magnesium silicate composite material according to claim 1, characterized in that: The content of amorphous SiO2 in the silica ash is greater than 95wt.%.

7. The straw / hydrated magnesium silicate composite material according to claim 1, characterized in that: The fly ash contains 50-60 wt.% of SiO2, 20-30 wt.% of Al2O3 and 5-8 wt.% of CaO.

8. The method for preparing the straw / hydrated magnesium silicate composite material according to any one of claims 1 to 7, characterized in that: The following steps are involved: Step 1: Mix the water reducing agent and water to obtain a liquid material; Step 2: Stir the gelling material thoroughly; add the liquid material in step 1 to the stirred gelling material, and stir thoroughly to obtain a hydrated magnesium silicate slurry; Step 3: adding the straw to the magnesium silicate hydrate slurry in step 2, and stirring thoroughly to obtain a straw / magnesium silicate hydrate slurry; Step 4: Pour the straw / hydrated magnesium silicate slurry obtained in step 3 into a mold, vibrate and then cure to obtain the desired straw / hydrated magnesium silicate composite material.

9. The method for preparing a straw / hydrated magnesium silicate composite material according to claim 8, characterized in that: In step 3, the mixture was first stirred for 30 seconds and then rapidly stirred for 6 minutes.

10. Use of the straw / hydrated magnesium silicate composite material obtained by any one of the preparation methods of claims 8 to 9, characterized in that: The straw / hydrated magnesium silicate composite material is used for building materials.